SISTEM AKUNTANSI ORGANISASI PENGELOLA ZAKAT (Mazahib, 2013)
Zakat institution is an institution that is in the middle so that the public has demanded transparency and accountability. In carrying out its activities as amyl, zakat organizations have principles that must be adhered to, including zakat organization must have a system of accounting and financial management, audit, and publication. By applying the principles of the organization's financial statements will be achieved in accordance with the zakat accounting standards.